2010
DOI: 10.1111/j.1365-2052.2009.02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the porcinetransferringene (TF ) and its association with disease severity following an experimentalActinobacillus pleuropneumoniaeinfection

Abstract: Transferrin (TF)-mediated provision of iron is essential for a productive infection by many bacterial pathogens, and iron-depletion of TF is a first line defence against bacterial infections. Therefore, the transferrin (TF) gene can be considered a candidate gene for disease resistance. We obtained the complete DNA sequence of the porcine TF gene, which spans 40 kb and contains 17 exons. We identified polymorphisms on a panel of 10 different pig breeds. Comparative intra- and interbreed sequence analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The fact that more than 50 App genes are involved in iron uptake and metabolism (Xu et al., ), some of which are differentially expressed during infection (Deslandes et al., ; Klitgaard, Friis, Jensen, Angen, & Boye, ), supports the major importance of this bacterial adaptation strategy for disease pathogenesis (Bossé et al., ). Genetically defined differences in disease susceptibility between breeding lines were, in part, due to differences in the iron‐transport protein transferrin, because different protein variants might be bound with variable intensity by the transferrin binding receptors of App (Daniłowicz et al., ; Reiner, Bertsch, et al., ).…”
Section: Disease Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that more than 50 App genes are involved in iron uptake and metabolism (Xu et al., ), some of which are differentially expressed during infection (Deslandes et al., ; Klitgaard, Friis, Jensen, Angen, & Boye, ), supports the major importance of this bacterial adaptation strategy for disease pathogenesis (Bossé et al., ). Genetically defined differences in disease susceptibility between breeding lines were, in part, due to differences in the iron‐transport protein transferrin, because different protein variants might be bound with variable intensity by the transferrin binding receptors of App (Daniłowicz et al., ; Reiner, Bertsch, et al., ).…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…Genetically defined differences in disease susceptibility between breeding lines were, in part, due to differences in the iron-transport protein transferrin, because different protein variants might be bound with variable intensity by the transferrin binding receptors of App (Daniłowicz et al, 2010;.…”
Section: Experimental Dual Infections With Swine Influenza Virus (Sivmentioning
confidence: 99%
“…Recent evidence for genetic resistance/susceptibility of pigs to A. pleuropneumoniae, a serious factor in worldwide pig production, comes from direct line comparisons (Hoeltig et al 2009;Benga et al 2009;Danilowicz et al 2009;Kahlisch et al 2009) and two QTL studies (Gregersen et al 2010;Reiner et al 2014). Gregersen et al (2010) mapped QTL for chronic pleuritis in a vast number of slaughter pigs, however, with minor accuracy regarding field phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data provided clear indications for a significant genetic difference in susceptibility to an A. pleuropneumoniae infection in challenged German breeding lines (Hoeltig et al 2009). The porcine transferrin gene (TF; Danilowicz et al 2009), glycoproteins (Kahlisch et al 2009), and immune markers (Benga et al 2009) have been regarded as potential corresponding biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Daniłowicz et al [83] identified 62 polymorphisms in TF genome sequence on a panel of 10 different pig breeds, but only found one possible association of the severity of A. pleuropneumoniae infection with TF genotypes. Cav1 was differentially expressed under H. parasuis infection, SNPs in this gene were found associated with blood parameter traits [89].…”
Section: Genetic Control Of Porcine Resistance To Gram-negative Bacilmentioning
confidence: 99%